Policy Implementation of The Jogo Tonggo Program In Tempelan, Blora District, Blora Regency - Charis Christiani; R.Permadi Mulajaya; Susanti (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2023)
To manage with Covid-19, the Governor of Central Java took a policy by issuing Governor's Instruction Number 1 of 2020 concerning Community Empowerment in Accelerating Covid-19 Response at the Community Unit Level (RW) through the Establishment of the Jogo Tonggo Task Force. This article aims to analyze the Implementation of the Jogo Tonggo Program in Tempelan Village, Blora Regency. The Jogo Tonggo movement developed and officially became a community activity unit to overcome the Covid-19 pandemic at the village level in Central Java Province. Tempelan Village is one of the villages with a relatively high positive case of Covid-19. This research uses qualitative research and data collection techniques through observation, interviews, and documentation. The results of this research are as follows: (a) Communication Aspects, the delivery of tiered information between the bureaucracy is good (b) Aspects of Resources, the parties involved in the implementation of Jogo Tonggo in Tempelan Village are the Head of hamlet as the head of the task force, with representatives being all heads of a neighbourhood, PKK, youth organizations, Linmas and all residents (c) The attitude of the implementers of Jogo Tonggo in Tempelan Village is good, supports each other and coordinates (d) Aspects of Bureaucratic Structure. The jogo tonggo task force characteristics are social and humanitarian, cooperation, and work non-permanently, meaning that the Jogo Tonggo task force exists only during a covid-19 pandemic. Cooperation and coordination run smoothly, both government and non-government/private institutions. For this reason, it is necessary to further develop the implementation of community empowerment-based policies in order to further strengthen social cohesion capital.